Case report: surgical removal of a migrated needle in right ventricle of an intravenous drug user - Xianming Fu; Kai Chen; Xiaobo Liao; Kangjun Shen (BMC, 2017)
Abstract Background Illicit drug use has become an increasing public health and social concern in the past decades worldwide. Intravenous injection has an elevated risk of infection. Needle embolism is a rare complication of intravenous drug users, Retained broken needles can lead to local complications, such as infection, but they also have the potential to embolize to heart or lung, and lead to serious complications. Method We reported a rare case of an intravenous drug user which a retained broken needle fragments in the inferior wall of the right ventricle. Results We performed a successful surgery and give our comments and recommendations for illicit drug use worldwide and in China. Conclusions Illicit Drug use becomes a global problem because of its health and social harmfulness. To help drug addicts and provide prevention and treatment services are the obligations and responsibilities of all medical workers.